Perspectives on the Sports Analytics Revolution: An Introduction to the Special Issue - Jun Kim (Journal of Applied Sports Management, 2022)
The goal of this special issue is to add to the academic literature on analytics by offering a diverse array of perspectives on the use of analytics and technology in sports. Sticking with the overall scope of the Journal of Applied Sport Management, the “think pieces” in this special issue are meant to be grounded in existing scholarship while allowing the invited authors a great deal of originality and flexibility to consider what may be coming next and how we, as sport professionals and scholars, can be prepared to meet the challenges and opportunities that are on the horizon.
Keywords: sport analytics